(untitled) (Journal of Face Aesthetics, 2021)
The aesthetic perception of a face is multifactorial. The researchers most often focus on its proportions in terms of historical beauty canons, anthropological intercultural gender and race differences, and a multi‑faceted approach to aging, also at the molecular level. This multifaceted nature is the result of both individual and holistic perception of the phenomenon of beauty, which as a visual aspect is susceptible to optical illusions and cultural definition.